Improved Isolation of Salmonellae from Naturally Contaminated Meat Products by Using Rappaport-Vassiliadis Enrichment Broth - Vassiliadis, Peter (1981)
A total of 454 specimens of meat products were examined for salmonellae by using five procedures of enrichment. The use of a selective motility medium, inoculated from enrichment in Muller-Kauffmann broth, resulted in an increase in the number of positive specimens. However, simple enrichment in Rappaport-Vassiliadis broth, after preenrichment, was more sensitive and specific for recovering salmonellae than the selective motility medium-Muller-Kauffmann broth method.